Geoinformation modeling for optimization of location of land parcels for apiaries - Moskalenko, A.; Domina, I. (Land Management, Cadastre and Land Monitoring, 2019)
The features of the selection of the area for placement of apiaries are analyzed, which will provide a sufficient forage base and productivity of apiaries and at the same time will be safe for the life of bees.The possibilities of using geoinformation models for finding the apiaries optimal location have been shown in the research. Finding suitable parcels in a fairly short time is due to the dependence on blossom of entomophily cultures. In the article, it was shown the analysis of different requires for location of bee-garden land parcels and the solution of the automation of work related to the preparation of geo-images of suitable territories.This research describes the algorithm for making the geo-images reduces waste the time consuming and accelerates the analysis of spatial data for making decisions on the location of apiaries. It was proposed to use spatial analysis for selecting the optimal location of apiary.As a result of the research, it was established that an algorithm that automate some steps in the creating of land management documentation for beekeeping farms can be used for the location determination of bee-garden land parcels. Key words: geoinformation modeling, bee forage, geo-image.